Design, synthesis, and biological evaluation of histone deacetylase inhibitor with novel salicylamide zinc binding group. Issue 17 (29th April 2022) - Kim, Ji Hyun; Ali, Khan Hashim; Oh, Yong Jin; Seo, Young Ho
Abstract: Introduction: Histone deacetylases (HDACs) have emerged as important therapeutic targets for various diseases, such as cancer and neurological disorders. Although a majority of HDAC inhibitors use hydroxamic acids as zinc binding groups, hydroxamic acid zinc-binding groups suffer from poor bioavailability and nonspecific metal-binding properties, necessitating a new zinc-binding group. Salicylic acid and its derivatives, well-known for their therapeutic value, have also been reported to chelate zinc ions in a bidentate fashion. This drew our attention towards replacing hydroxamic acid with salicylamide as a zinc-binding group. Methods: In this study, for the first time, compound 5 possessing a novel salicylamide zinc-binding group was synthesized and evaluated biologically for its ability to inhibit various HDAC isoforms and induce acetylation upon α-tubulin and histone H3 among MDA-MB-231 cells. Results: Compound 5 exhibits selective inhibition against class I HDAC isoforms (HDAC1, 2, and 3) over class II and IV HDAC isoforms (HDAC4, 6, and 11). The exposure of MDA-MB-231 cells to compound 5 efficiently induced the acetylation of more histone H3 than α-tubulin, suggesting that compound 5 is a class I selective HDAC inhibitor. Moreover, the molecular docking study indicated that the salicylamide zinc-binding group of compound 5 coordinates the active zinc ion of class I HDAC2 in a bidentate fashion. Conclusion: Overall, salicylamide represents a novel zinc-binding group for the development of class I selective HDAC inhibitors. Graphical abstract: (http://links.lww.com/MD/G668 )